نظرية الفن الإسلامي عند المفكر إسماعيل الفاروقي - إدهام محمد حنش (International Institute of Islamic Thought, 2013)
قدم إسماعيل الفاروقي نظريته للفن الإسلامي التي تقوم على الكشف عن العلاقة القيمية الحميمة بين التوحيد والجمال، والنظر إلى القرآن الكريم بوصفه المأثرة الفنية الأولى. وهذا البحث هو مراجعة نقدية لمشروع الفاروقي المعرفي في بناء هذه النظرية الفن، وإثارة بعض الملحوظات حول جهد الفاروقي في بيان مفهوم الفن الإسلامي، وتعزيز هذا الجهد في دراسة الفن في الفكر الاسلامي وآفاقه الفلسفية والتاريخية، بقصد التوصل الى إطار معرفي لنظرية الفن الإسلامي يتسم بالوضوح. This paper presents Ismail al-Faruqi's theory of Islamic art, which is based on the exposition of the special value-based relationship between Tawhid and aesthetics, and considering the Holy Qur'an as the prime artistic feat. This paper is a critical review of al-Faruqi's epistemological project in building his theory on art, and raises some observations on al-Faruqi's effort in expounding on the concept of Islamic art, and promoting efforts to study art from the perspective of Islamic thought in its philosophical and historical prospects, with the aim of reaching a clear and coherent epistemological framework for the theory of Islamic art.